2017
DOI: 10.1113/ep086092
|View full text |Cite
|
Sign up to set email alerts
|

Activation of protease‐activated receptor 2 mediates cutaneous vasodilatation but not sweating: roles of nitric oxide synthase and cyclo‐oxygenase

Abstract: What is the central question of this study? Protease-activated receptor 2 (PAR2) is located in the endothelial cells of skin vessels and eccrine sweat glands. However, a functional role of PAR2 in the control of cutaneous blood flow and sweating remains to be assessed in humans in vivo. What is the main finding and its importance? Our results demonstrate that in normothermic resting humans in vivo, activation of PAR2 elicits cutaneous vasodilatation partly through nitric oxide synthase-dependent mechanisms, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 52 publications
3
10
0
Order By: Relevance
“…It is also known that keratinocytes release prostaglandins (PG) through PAR-2 (protease-activated receptor 2), promoting melanocyte dendricity and transfer of melanosomes to keratinocytes (25). COX has also been implicated in the PAR-2 pathway (26). We hypothesise that COX inhibition of DSHA (24) over keratinocytes would reduce PG release mediated through PAR-2, thus decreasing PG-induced melanocyte dendricity and, consequently, reducing transfer of melanin to keratinocytes, which would decrease mottled pigmentation in RCM exploration corresponding to a decreased pigmentation of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that keratinocytes release prostaglandins (PG) through PAR-2 (protease-activated receptor 2), promoting melanocyte dendricity and transfer of melanosomes to keratinocytes (25). COX has also been implicated in the PAR-2 pathway (26). We hypothesise that COX inhibition of DSHA (24) over keratinocytes would reduce PG release mediated through PAR-2, thus decreasing PG-induced melanocyte dendricity and, consequently, reducing transfer of melanin to keratinocytes, which would decrease mottled pigmentation in RCM exploration corresponding to a decreased pigmentation of epidermal keratinocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Direct evaluation of this possibility is required, as previous studies have demonstrated that substances which can cause cutaneous vasodilatation under normothermic resting conditions do not necessarily lead to cutaneous vasodilatation during wholebody heat stress or local heating [14,15]. While we observed an influence of the PAR2 agonist on cutaneous vasodilatation during normothermic resting, there was no effect of PAR2 activation on sweating during normothermic rest [13]. However, the lack of an effect is not surprising given that the modulation of the sweating may only occur when the sweat gland is pre-activated [16].…”
Section: Introductionmentioning
confidence: 43%
“…Thereafter, the fibres were continuously perfused in a counterbalanced manner with: 1) lactated Ringer solution (Control) 2) 0.05 mM, 3) 0.5 mM, or 4) 5 mM of the PAR2 agonist, SLIGKV-NH 2 (Alomone labs, Jerusalem, Israel). The concentrations of SLIGKV-NH 2 were selected based on our previous work [13]. The agents were perfused through the fibre at a rate of 4 μL•min −1 via a microinfusion pump (Model 400, CMA Microdialysis, Solna, Sweden) for at least 60 min to ensure PAR2 receptor activation with SLIGKV-NH 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations